Sketch Worksheets: A Sketch-Based Educational Software System - Yin, Panrong; Forbus, Kenneth; Usher, Jeffrey; Sageman, Brad; Jee, Benjamin (Proceedings of the AAAI Conference on Artificial Intelligence, 2010)
Intelligent tutoring systems and learning environments can provide important benefits for education, but few have been developed for heavily spatial domains. One bottleneck has been the lack of rich models of visual and conceptual processing in sketch understanding, so that what students draw can be interpreted in a human-like way. This paper describes Sketch Worksheets, a form of sketch-based educational software that mimics aspects of pencil and paper worksheets commonly found in classrooms, but provides on-the-spot feedback and support for richer off-line assessments. The basic architecture of sketch worksheets is described, including an authoring environment that allows non-developers to create them and a coach that uses analogy to compare student and instructor sketches as a means to provide feedback. A pilot experiment where sketch worksheets were used successfully in a college geoscience class in Fall 2009 is summarized to show the potential of the idea.